Beneath the City: Unearthing Naples' Archaeological Underground for New Urban Continuity - Chiara Barone (Journal of Contemporary Urban Affairs, 2023)
This study explores the potential of connecting the visible cityscape with concealed subterranean spaces, aiming to reshape urban continuity. It departs from the traditional perception of underground areas as purely technical domains, seeking fresh perspectives on inhabiting these concealed environments. Using three Naples locations as case studies, we develop a methodology applicable to similar urban contexts, emphasizing the archaeological underground's ability to trigger socio-economic transformations. Accordingly, it advocates for deliberate design interventions to reintegrate the archaeological underground into contemporary urban dynamics, offering strategies to redefine the relationship between city dwellers and their urban environment. Through case studies and visual representations, the study presents design solutions that enhance the use of subterranean spaces, fostering accessibility, community engagement, and cultural preservation. These initiatives promote enduring economic sustainability, potentially benefiting other cities facing similar challenges, and creating a harmonious connection between archaeological underground layers and the modern urban fabric. In summary, this research underscores the vast potential of subterranean spaces for future urban development, requiring innovative methodologies and technological integration to shape a unified and adaptable cityscape.